(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
Experiential media (EM) technologies such as augmented reality (AR) allow users to make practical contact with or experience the phenomena virtually. Using the qualitative content analysis technique, this study seeks to understand the role of AR, particularly AR filters, in Black Lives Matter (BLM), Climate Change, and COVID-19 social movements, where all three social movements are inextricably connected and dependent on each other. The pertinent concept across these movements is the emergent norm – a sense of just and unjust – central to these movements (Turner, 1969). Taking such a triadic approach (interconnecting social movements) and using the Experiential Media theoretical framework (Pavlik, 2018), this study seeks to understand what types, themes, and to what extent EM qualities are utilized by AR filters offered on (1) Instagram and (2) Snapchat platforms pertaining to (1) BLM, (2) Climate Change, and (3) COVID19 (Vaccination, Social Distancing, and Wear a Mask) social movements. Using an iPhone 12 Pro Max smartphone with Light Detection and Ranging (LiDAR) sensor for a seamless AR experience, a total of 466 AR filters were experienced, and observations were recorded in the form of memos for data analysis. This study establishes and explores the existence of AR filters on social movements and dovetails with the existing literature. The potential outcome could be to understand how something that seems trivial and playful as AR filters can help communicate politically for social change and how EM can transform social movements by creating an immersive virtual sphere for the global and local to come together for social change.